FACTORS THAT CONTRIBUTE TO RAPE IN MALAYSIA - Mohd Al Faani Mokhtar Rudin, Ahmad Jazimin Jusoh (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The development of social problems in Malaysia, especially that involving rape and sexual assaults, has seen a serious escalation. This study intended to determine factors that make adolescents vulnerable to rape. The methodology used in this study was the case study method. Nine trainees from the Adolescent and Children Protection Centre were chosen and interviewed as study samples. The NVivo 12 software was used to analyse the findings. This study found that seven factors had influenced the vulnerability of adolescents to rape, such as the victims themselves, parents, internet and technology, family background, education, peer influence as well as society and the government. Hence, this study has provided important information to all interested parties that can be helpful when planning preventive programs and treatments for cases related to rape.